Semantic Analysis on Advertisement Slogan’s - Dwi Fita Heriyawati; Fitria Febriyan (ELITE Association Indonesia, 2019)
The objective of this study is to analyze types of meaning that used on the advertisement slogan’s This study used descriptive qualitative. The instrument of this research is the researchers herself. The main data was collected by taking a screenshot from the website of beauty, electronic, and technology product. The researchers found 42 types of meaning in 30 advertisement slogans which were published from March up to May 2019. To clarify the accuracy of the data, the researchers used theory and investigator triangulation. The results showed that connotative meaning is the most type of meaning with 31%, reflected meaning or situational meaning had 24%, affective meaning is 17%, 10% for social meaning or socio-cultural meaning, conceptual meaning or lexical meaning and collocative meaning or textual meaning with 7%. The lowest type of meaning is thematic meaning with 5%. Thus, the types of meaning created an expressive, influential, and impactful advertising slogans.